Composition of planktonic foraminifera test-bound organic material and implications for carbon cycle reconstructions - Paoloni, Tommaso; Hoogakker, Babette; Navarro Rodriguez, Alba; Pereira, Ryan; McClymont, Erin L.; Jovane, Luigi; Magill, Clayton (Frontiers in Marine Science, 2023)
Introduction Foraminiferal shells are extensively used to reconstruct the marine environment in the geological past. The foraminifera test-bound organic material (FBOM), sheltered by the test from potential diagenetic alteration and contamination, has great feasibility to improve our understanding of carbon and nitrogen cycling. The FBOM δ13C has been proposed as a proxy for reconstructing past environmental conditions. However, to fully exploit the proxy potential of FBOM, its molecular composition and the influence of the latter on the FBOM δ13C need to be assessed. Method Here we use a novel combination of gas chromatography-mass spectrometry, flame ionization detection (GC-MS/FID) and liquid chromatography organic carbon and nitrogen detection (LC-OCD/ OND) analyses to study the FBOM chemical composition. Results Our results indicate that polysaccharides and proteins dominate FBOM, as proposed by earlier studies, with no evidence of detectable lipids (alkyl lipids, trimethylsilyl ethers of fatty alcohols, trimethylsilyl esters of fatty acids and steranes derivatives were targeted). Discussion Previous studies suggested that FBOM δ13C may be used to reconstruct past atmospheric CO2 concentrations. However, our results indicate that the use of FBOM δ13C to reconstruct CO2 carries an approximate uncertainty of ±21 ppm for past atmospheric CO2 abundance. We suggest that FBOM δ13C can be used as a novel proxy to reconstruct particulate organic material (POM) δ13C. This is also supported by the recently confirmed minor fractionation between POM and FBOM δ13C.